2013
DOI: 10.1186/1750-9378-8-18
|View full text |Cite
|
Sign up to set email alerts
|

Recent cancer incidence trends in an observational clinical cohort of HIV-infected patients in the US, 2000 to 2011

Abstract: BackgroundIn HIV-infected populations in developed countries, the most recent published cancer incidence trend analyses are only updated through 2008. We assessed changes in the distribution of cancer types and incidence trends among HIV-infected patients in North Carolina up until 2011.MethodsWe linked the University of North Carolina Center for AIDS Research HIV Clinical Cohort, an observational clinical cohort of 3141 HIV-infected patients, with the North Carolina Cancer registry. Cancer incidence rates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Five-year survival increased from 63% during the pre-HIV era to 72% during HAART. Yanik et al 28 examined more recent trends linking the University of North Carolina (NC) Center for AIDS Research HIV Clinical Cohort, an observational clinical cohort of 3141 HIV-infected patients 30% of whom were female, with the NC Cancer registry data between 2000 and 2011. Across 15,022 person-years of follow-up, 202 cancers were identified with most being virus-related (incidence rate (IR) per 100,000 person-years was 1345; 95% CI: 1166-1544).…”
Section: Anal Hpv Infection and Disease In Womenmentioning
confidence: 99%
“…Five-year survival increased from 63% during the pre-HIV era to 72% during HAART. Yanik et al 28 examined more recent trends linking the University of North Carolina (NC) Center for AIDS Research HIV Clinical Cohort, an observational clinical cohort of 3141 HIV-infected patients 30% of whom were female, with the NC Cancer registry data between 2000 and 2011. Across 15,022 person-years of follow-up, 202 cancers were identified with most being virus-related (incidence rate (IR) per 100,000 person-years was 1345; 95% CI: 1166-1544).…”
Section: Anal Hpv Infection and Disease In Womenmentioning
confidence: 99%
“…Studies of adjusted IR time trends that classified NADC into broad groupings have produced inconsistent results [20, 2325]. Evidence supports decreasing trends for lung cancer and Hodgkin lymphoma and an increasing trend for liver cancer, but results for anal cancer have been inconsistent; many nonsignificant trends for specific NADC have been observed, perhaps due to insufficient statistical power [11, 1619, 2123, 26]. The ADC adjusted IR has continued to decline during the ART era [9, 11, 17, 18, 20, 23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of cancer cases in this study that was ADCs was lower than previously reported [2224]. Among HIV-infected cancer cases, about half were ADCs in an Italian study [22], one-third were ADCs in a single institution study in the US [23], and 60% were ADCs in an Australian observational database [24]. Our finding of the decline with age in the proportion of cancers that are ADCs is consistent with reports on the age-related decline in cancers attributable to infectious agents [25, 26].…”
Section: Discussionmentioning
confidence: 64%